Ludic form and contemporary performance arts. - Kirkpatrick, Graeme (Journal for Cultural Research, 2018)
Four performance artists who have used computer games in their work were interviewed for their reflections on aspects of that process, including the decision to make use of games; difficulties and challenges entailed by that choice, and aesthetic values realized in implementing it. Their reflections are related to foundational questions of computer game studies, especially the question of what computer gameness consists in. The main argument draws on Adorno's writing on theatre, specifically his suggestion that audience participation might carry utopian potential. The idea of 'ludic form' is put forward as an attempt to grasp positive fulfilments of this in contemporary performance, especially the performance of space. The aesthetics of ludic form turn on use of a succession of mild shocks to stimulate and guide the audience through that process, rather than creation of an immersive or 'gamified' audience experience.